2014
DOI: 10.1111/nmo.12450
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus rhamnosus GG (LGG) and prebiotic prevent neonatal inflammation‐induced visceral hypersensitivity in adult rats

Abstract: Results document that in rats LGG can attenuate neonatally induced chronic visceral pain measured in adulthood. Prolonged intake of LGG alters some key brain neurotransmitters and biogenic amines that could be involved in pain modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 54 publications
0
35
0
Order By: Relevance
“…In keeping with previously published work from our own laboratory, we saw an increased visceral sensitivity in MS rats (Felice et al., ; O'Mahony et al., ), which was improved with the consumption of MFGM. We and others have previously shown that dietary interventions targeting the gut microbiota reduce visceral sensitivity in several different animal models (Kannampalli et al., ; Larauche, Mulak, Yuan, Kanauchi, & Tache, ; McVey Neufeld et al., ; Wang et al., ). Yet here while we do not see striking differences in the microbiota profile of the control diet‐fed MS and NS rats, the MS rats do display a significant increase in visceral sensitivity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In keeping with previously published work from our own laboratory, we saw an increased visceral sensitivity in MS rats (Felice et al., ; O'Mahony et al., ), which was improved with the consumption of MFGM. We and others have previously shown that dietary interventions targeting the gut microbiota reduce visceral sensitivity in several different animal models (Kannampalli et al., ; Larauche, Mulak, Yuan, Kanauchi, & Tache, ; McVey Neufeld et al., ; Wang et al., ). Yet here while we do not see striking differences in the microbiota profile of the control diet‐fed MS and NS rats, the MS rats do display a significant increase in visceral sensitivity.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, this is the first study to show that MFGM consumption results in a significant reduction of the early-life stress-induced visceral hypersensitivity. While previous studies have shown that dietary supplementation with probiotics and prebiotics is effective in the reduction of visceral sensitivity (Kannampalli et al, 2014;McKernan, Fitzgerald, Dinan, & Cryan, 2010;McVey Neufeld et al, 2017;Wang et al, 2017), the impact of MFGM has not been shown before.…”
Section: Discussionmentioning
confidence: 97%
“…57 Interestingly, vancomycin treatment did not impact cognitive or anxiety-related behaviors, growth or other parameters in the adult animals. Recently, Kannampali and colleagues 58 used the rat chronic visceral hypersensitivity model to test the effect of probiotics and prebiotics on ameliorating the severity of neonatal stress-induced hypersensitivity.…”
Section: Altered M Icrobiome During Early Life Critical Sensitive Permentioning
confidence: 99%
“…The previous studies had the various recovery duration between 0 to 7 days after EMG surgery. [32][33][34][35][36][37] We allowed the rats recovery duration after surgery to be at least 2 days. EMG surgery might induce local inflammation and there is a possibility that inflammation increases VMR for colorectal distention.…”
Section: Cgrpmentioning
confidence: 99%